ANALISIS SEKTOR PARIWISATA DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KABUPATEN SOLOK TAHUN 2000-2011 - Susanti, Delmitha; Ansofino, Dr.; Afriza, M.Pd, Rina (Pendidikan Ekonomi, 2014)
Abstract This research was about the relationship between tourism potency, the total of tourist and hotel guests toward the improvement of local reveniuw Kabupaten Solok. The analysis used was multi linear regression by using secondary data obtained from Dinas Kebudayaan dan Pariwisata (DIBUDPAR), Dinas Pendapatan dan Pengelolaan Keuangan dan Aset Daerah (DPPKA), and Badan Pusat Statistik (BPS) of Kabupaten Solok.The result showed that first,there was positive correlation between tourism potency and PAD in Kabupaten Solok. It was showed through the cooefficient relation (178.562) on which t-obtained (5.423) was bigger than t-table (1.895) and the probability wad smaller than significant level. Second, there was positive correlation between the total of tourist toward PAD which was showed through correlation coefficient (26.172) in which t-obtained (6.338) was bigger than t-table (1.895) and the probability was smaller than significant level.third, there was positive correlation between the hotel guests toward PAD which was showed by the coefficient correlation (15.264) in which t-obtained (2.978) was bigger than t-table (1.895) amd the propobility was smaller than the significant level. The R square waa 0.977 which means that 97.7% of PAD was obtained from the tourism potency,the total of tourist and the hotel guest.